Ambiguity, Inference, and Relevance in Kurdish Humour - Shakir, Nadia; AL-Bajjari, Ismael F. Hussain (Journal of Cultural Analysis and Social Change, 2026)
This study explores the interaction between ambiguity, inference, and relevance in Kurdish humour discourse within a pragmatic framework. It attempts to investigate how ambiguous Kurdish expressions: lexical, syntactic, or pragmatic, function as cognitive shooters that lead listeners toward humourous interpretations through processes of inferencing. Intentional ambiguity is the basic element that humour in both Kurdish and English often relies on. It requires the listeners to select among competing interpretations and reach optimal relevance. By analyzing a set of Kurdish humourous written and spoken conversations, the study detects the pragmatic mechanisms through which humour is structured and built via the interaction between prearranged meaning and contextual inference. The findings show that ambiguity should not be considered a communicative failure, but it is a strategic method that requests inferential engagement, producing cognitive pleasure and surprise. The present research highlights the universality of inferential humour processing while emphasizing culture-specific patterns in Kurdish humour construction and comprehension.